Correlation Of Soil Physico-Chemical Fctors With Vam Fungi Distribution Under Different Agroecological Conditions - SNOBER H. BHAT,; AFSHANA BASHIR DARZI,; MOHD SHAHIJAHAN DAR,; MASOOD MAJAZ GANAIE,; SAJAD HUSSAIN BAKHSHI, (International Journal of Pharma and Bio Sciences, 2011)
An attempt was made to analyze the correlation between the physical and chemical factors of soil with the distribution of VAM fungi under different Agroecological condition. Two fields from Chandur Bazar Tehsil of Amravati district were selected for the present investigation because the edaphic factors of the particular district show highly variable soil geography. The study revealed that all the physical and chemical factors viz; soil moisture, soil texture, soil pH and EC, nitrogen, Phosphorus, Potassium and Carbon are positively correlated with the distribution of VAM fungi